Asymmetric conjugate addition of grignard reagents to 3-silyl unsaturated esters for the facile preparation of enantioenriched β-silylcarbonyl compounds and allylic silanes - Zhao, Kai (2015)
A highly enantioselective conjugate addition of Grignard reagents to 3-silyl unsaturated esters to deliver synthetically useful chiral β-silylcarbonyl compounds was developed. The synthetic value of this methodology was further illustrated by the synthesis of enantioenriched β-hydroxyl esters and the facile access granted to various α-chiral allylic silanes. A plethora of diastereoselective transformations of β-silylenolates were also investigated and afforded manifold organosilanes that contained contiguous stereogenic centers with excellent enantioselectivity.